Experimental and Numerical Analysis of PIP Slip Joint Subjected to Bending - Md Ariful Islam; Hongbae Park; Daeyong Lee (Journal of Marine Science and Engineering)
Detachable circular hollow sections (CHSs) offer an innovative solution to tackle the complexities of installation, maintenance, upgrades, and repairs in offshore monopile systems, particularly in challenging environments with limited access. As an alternative to traditional tubular joints, the PIP slip joint presents advantages in terms of ease of installation, time efficiency, and reduced susceptibility to failure. This study conducts an experimental investigation on PIP (Pile-in-Pile) slip joints under pure bending conditions, accompanied by comprehensive numerical analyses to examine the relationship between section slenderness, contact properties, and structural performance. The results highlight a strong correlation between force-displacement curves and include a comparison of compressive and tensile strain values for both experimental and numerical models. The experimental and numerical models showed strong agreement across all results, demonstrating the robustness of the findings. Additionally, numerical models were utilized to investigate various D/t ratios, revealing insights into the normalized moment, rotational capacity, and the impact of local buckling and contact mechanics. Furthermore, a comparison of these findings with established code guidelines, such as Eurocode and AISC-LRFD, has been conducted and reviewed in the context of this study. From analysis, it was found that the rise in the D/t ratio prompted a transformation in the buckling mode, which substantially altered the rotational ratio. This shift indicates the importance of understanding how these variables interact in engineering applications. These findings significantly enhance the understanding of PIP slip joints and emphasize their potential as a compelling alternative for offshore wind turbine support structures.